The effectiveness of fuel reduction burning for wildfire mitigation in sclerophyll forests. Issue 4 (1st October 2020) - Hislop, S.; Stone, C.; Haywood, A.; Skidmore, A.
ABSTRACT: The wildfires in south-eastern Australia in the 2019–20 fire season were some of the worst in recent memory. The effectiveness of fuel-reduction burning as a risk mitigation strategy is, once again, being scrutinised. Some argue that more fuel-reduction burning is needed, while others suggest that it is of limited use in such extreme fires. In this study, we tested the effectiveness of fuel-reduction burning at a landscape scale in terms of its ability to reduce the severity of subsequent wildfire. To achieve this, we selected all the recent (2015–2019) fuel-reduction burns undertaken in New South Wales and Victoria that intersected with the extent of the 2019–20 wildfires and evaluated whether the fire severity was significantly different in the recently treated areas to that of similar untreated areas in the vicinity. To determine fire severity, Sentinel 2 satellite imagery and the change in normalised burn ratio (a common metric used for rapid and broadscale fire severity mapping) was used. Our results showed that 48% of the 307 recent fuel-reduction burns resulted in statistically significant decreased fire severity. Our results also indicated that more recent fuel-reduction burns had a greater impact, with 66% of burns undertaken in 2019 significantly reducing severity, compared with 42% from 2015. We also analysed each fuel-reduction burn in the context of a range of metrics, including location, elevation, slope, aspect and forest heterogeneity, to assess whether these factors influenced the likelihood that a burn would be effective. Location and, to a lesser degree, forest heterogeneity were found to be significant factors. Our results support the view that recent fuel-reduction burns reduce fire severity. It is unclear, however, whether the differences would be operationally significant under extreme conditions, when wildfires are driven largely by weather, irrespective of fuel loads.